An Investigation for Steganalysis in Color Images - Samah Aziz; Ahmed Nori (Al-Rafidain Journal of Computer Sciences and Mathematics)
With science developing and techniques used in Information hiding, there are another techniques wall together for Steganalysis. Steganography is considered as the new and the complementary system of Cryptography that took a long time in transferring secret and important messages through the networks Internet. Then there was the emergence of what complements Steganography as a science that analysis and discover the content of the secret messages and this science is Steganalysis. This study tackled and manifested the ideas of analysis processes that can be followed to interpret the secret messages and discovering them either by means of knowing about their existence only or the capability of extracting them in full. The work relied on two important technologies; the first is called the Support Vector Machine (SVM) and the second is called Fisher Linear Discriminator (FLD). The SVM technology has been used with the blind application idea while FLD has been used with the blind and non-blind application ideas using colored images which are PNG and BMP. Results proved the high efficiency of the two technologies in detecting the image that includes the secret messages and comparisons were varied between the two technologies in terms of detection rate, fault and the execution time.